2021
DOI: 10.12669/pjms.37.2.2647
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Modulated Arc Therapy (VMAT): A modern radiotherapy technique - A single institutional experience

Abstract: Objective: To evaluate VMAT plans for conformity and homogeneity of radiation dose to the target in order to share our experience as a pioneering institute to use VMAT technology in Pakistan. Methods: Since December 2014 to January 2018, 530 patients of various anatomical sites were treated by VMAT technique at Neurospinal Cancer Care Institute (NCCI) Karachi Pakistan. ERGO++ planning system (Version 1.7.2) was used to develop VMAT plans with single or multiple arcs by the rotation of couch and gantry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In comparison to IMRT, VMAT typically uses fewer monitor units (MUs), which can decrease the risk of secondary malignancy. 154 Navarria et al found that VMAT has superior dose conformity compared to 3DCRT and spares the healthy brain at medium to high doses in high-grade astrocytoma. 155 In low-grade astrocytoma, inhomogeneity and conformity did not differ significantly between VMAT and IMRT, while VMAT was related to a significant reduction of Mus.…”
Section: Treatmentmentioning
confidence: 99%
“…In comparison to IMRT, VMAT typically uses fewer monitor units (MUs), which can decrease the risk of secondary malignancy. 154 Navarria et al found that VMAT has superior dose conformity compared to 3DCRT and spares the healthy brain at medium to high doses in high-grade astrocytoma. 155 In low-grade astrocytoma, inhomogeneity and conformity did not differ significantly between VMAT and IMRT, while VMAT was related to a significant reduction of Mus.…”
Section: Treatmentmentioning
confidence: 99%